2017
DOI: 10.18203/2349-3933.ijam20171512
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adverse drug reaction of first line anti - tuberculous drugs on treatment outcome of tuberculosis under revised national tuberculosis control programme

Abstract: Background: Tuberculosis (TB), an infectious disease caused by Mycobacterium tuberculosis, is the major health care burden responsible for morbidity and mortality. The objective was to study the profile of adverse drug reactions (ADRs) and its outcome.Methods: It was a prospective observational study conducted in one of the RNTCP centre of Ahmedabad district. All TB patients visiting and taking short course of directly observed treatment (DOTS) were enrolled and monitored for ADRs. All the ADRs spontaneously r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Incidence of ADR was higher in females compared to males. In contrast to this, a study conducted by Dedun AR et al 19 showed that incidence of ADRs was more common in males. The reason for more occurrences of ADRs in females might be due to female's different life stages like pregnancy, menarche which modifies the drug response.…”
Section: Discussionmentioning
confidence: 75%
“…Incidence of ADR was higher in females compared to males. In contrast to this, a study conducted by Dedun AR et al 19 showed that incidence of ADRs was more common in males. The reason for more occurrences of ADRs in females might be due to female's different life stages like pregnancy, menarche which modifies the drug response.…”
Section: Discussionmentioning
confidence: 75%
“…The overall prevalence of ADRs with FLDs is estimated to vary from 2.3 to 17% in various Indian studies. 7,[15][16][17] A study conducted by Mehrotra observed that the prevalence of ADRs in the initial intensive phase was 17.39%. 15 Another study conducted at a tertiary institute in Calcutta observed that the overall toxicity was found in 35% cases in the daily regimen group, whereas it was found to be 27.9% in the intermittent regimen group.…”
Section: Epidemiology Of Adverse Drug Reactions With First-line Anti-mentioning
confidence: 99%
“…15 Another survey in Malaysia reported an ADR incidence of 15.8%; while a study done in Gujarat, India reported an incidence of 7.9%. 19,20 One possible explanation of this variation could be differences in detecting methods of ADRs. As to whether ADRs were collected based on face to face interview with patients and chart review, or retrospectively from patient's medical records, besides genetic makeup could also have played a role.…”
Section: Figure 2: Causality Assessment (Who-umc)mentioning
confidence: 99%
“…23 Similar results have also been reported by Dedun et al, but there are some studies suggesting females to be at higher risk of developing more ADRs. 20,24 It might be because they pass through life stages like pregnancy, menarche and menopause that has an impact on the drug response. 25 Studies done by Aamir et al, and Hassan et al, also had found ADRs to occur more commonly in females than males.…”
Section: Figure 2: Causality Assessment (Who-umc)mentioning
confidence: 99%